Mouse strain-specific responses along the gut-brain axis upon fecal microbiota transplantation from children with autism - Naika Prince; Lucia N. Peralta Marzal; Léa Roussin; Magali Monnoye; Catherine Philippe; Elise Maximin; Sabbir Ahmed; Karoliina Salenius; Jake Lin; Reija Autio; Youri Adolfs; R. Jeroen Pasterkamp; et al. (Gut Microbes)
Several factors are linked to the pathophysiology of autism spectrum disorders (ASD); however, the molecular mechanisms of the condition remain unknown. As intestinal problems and gut microbiota dysbiosis are associated with ASD development and severity, recent studies have focused on elucidating the microbiota-gut-brain axis’ involvement. This study aims to explore mechanisms through which gut microbiota might influence ASD. Briefly, we depleted the microbiota of conventional male BALB/cAnNCrl (Balb/c) and C57BL/6J (BL/6) mice prior to human fecal microbiota transplantation (hFMT) with samples from children with ASD or their neurotypical siblings. We found mouse strain-specific responses to ASD hFMT. Notably, Balb/c mice exhibit decreased exploratory and social behavior, and show evidence of intestinal, systemic, and central inflammation accompanied with metabolic shifts. BL/6 mice show less changes after hFMT. Our results reveal that gut microbiota alone induce changes in ASD-like behavior, and highlight the importance of mouse strain selection when investigating multifactorial conditions like ASD.